Hemichannels in neurodegenerative diseases: is there a link to pathology? - Bosch, Megan; Kielian, Tammy (Frontiers in Cellular Neuroscience, 2014)
Although originally considered a structural component of gap junctions, connexin hemichannels (HCs) are now recognized as functional entities capable of influencing metabolic gradients within the CNS, allowing direct communication between the intra- and extracellular milieus. Besides connexins, HCs can also be formed by pannexins, which are not capable of gap junction assembly. Both positive and negative effects have been attributed to HC activity in the context of neurodegenerative diseases. For example, HCs can exert neuroprotective effects by promoting the uptake of neurotoxic molecules, whereas chronic HC opening can disrupt molecular gradients leading to cellular dysfunction and death. The latter scenario has been suggested for multiple neurodegenerative disorders, including Alzheimer’s Disease and more recently, lysosomal storage disorders, which are the focus of this review. Currently available evidence suggests a complex role for HCs in neurodegenerative disorders, which sets the stage for future studies to determine whether targeting HC action may improve disease outcomes.